Some Notes about the Educational Inequality in Latin America - Guillermina Tiramonti (Universidad Autónoma de Madrid, 2016)
The purpose of this paper is to analyse the ways in which different Latin American countries have faced the permanent tension between include and differentiate the schooling population. Each country has generated historical conditions and traditions that determine the ways of processing this tension. For some countries, merit and exams are the criteria for justifying the unequal distribution of diplomas and awards. Other countries have chosen a system of open competition where actors mobilize different personal resources that define the unequal results. Finally, the conception of knowledge of modern schooling and its discriminative potential is discussed.